Mechanical, wear and thermal conductivity characteristics of snail shell-derived hydroxyapatite reinforced epoxy bio-composites for adhesive biomaterials applications - Oluwole Oladele, Isiaka; Onuh, Linus; Taiwo, Anuoluwapo Samuel; Borisadea, Sunday; Itua Agbeboh, Newton; Lephuthing, Senzeni Sipho (Taylor and Francis, 2022)
This research investigates the effects of snail shell-based hydroxyapatite (HAp) reinforcements on the mechanical, wear, and selected physical properties of epoxy-based composites. The exploitation of these properties was aimed at assessing the suitability and efficiency of the developed bio-composites for adhesive biomedical applications. Snail shell wastes were sourced and processed to obtain (HAp) particles of ˂20 μm. The bio-derived hydroxyapatite-based epoxy composites were produced using the stir-cast method by mixing the hydroxyapatite with the epoxy resin and hardener before pouring into the moulds where they are allowed to cure. Scanning Electron Microscope (SEM) and X-ray Diffraction (XRD) of the snail shell hydroxyapatite particles were carried out while mechanical, wear, and physical properties of the developed composites were evaluated. SEM images of the fracture surfaces were also examined. The results showed that enhancements occurred from the addition of snail shell-derived HAp to epoxy resin in the developed composites. The results revealed that most of the properties gave their optimum values when 15 wt.% reinforcement was used. At this weight fraction, optimum values were obtained which include 43 MPa for maximum flexural strength, 40HS for hardness, 40 J for impact, 0.35 W/mK for thermal conductivity, and 0.07 for wear index.
Keywords: adhesive biomaterial; orthopaedic; bio-derived; hydroxyapatite; biocompatible; biodegradable